Analisis Faktor-Faktor yang Mempengaruhi Keputusan Petani Memilih Usahatani Jagung Manis Hibrida di Desa Bocek Kecamatan Karangploso Kabupaten Malang - Siti Nurbaiti; Farida Syakir; Dwi Susilowati (Program Studi Agribisnis, 2020)
The purpose of this research is 1) to know the feasibility of a hybrid sweet corn farming in the village of Bocek Karangploso District Malang 2) to know the factor-fakor that affects the decision of the hybrid sweet corn farming. The methodology of the regional weaver of the research is done by Purposive in the village of Bocek Karangploso District Malang. This is because of the consideration that the region is one of the producers of Sweet corn hybrid in Malang regency. While the research time is conducted in October-November. Sampling of farmers was conducted with non random sampling techniques, known numbers of hybrid sweetcorn farmers in village Bocek as much as 150 farmers samples taken as much as 40 or 27% and 105 farmers for local corn samples taken as much as 20 or 19% . Processing and analysis of data is done in a deskritif, data collection used is primary data and secondary data. It can be known that the feasibility of a hybrid sweet corn farming in the village of Bocek Karangploso District for farming is decent, this is seen from the R/C ratio of 1.9. So the farming is worth applying. Farming system is profitable because the R/C Rationya value is greater than 1. The results of the study obtained with a value of G 46,458 showing the regression of the logistics model as a whole can explain the decision of farmers to choose the hybrid sweet corn farming, factor factor that affects the decision of farmers to choose hybrid sweet corn farming is the level of education, total family dependents and income. Keywords: decision, feasibility of hybrid sweet corn farming, Logit Model